PENERAPAN MODEL PEMBELAJARAN SEARCH SOLVE CREATE SHARE UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS XI IPS 1 SMA NEGERI 1 BANGKINANG KOTA - Lona Sari; Zulkarnain Zulkarnain; Putri Yuanita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is classroom action research that aims to improve of learning process and to improve mathematics achievement with applied the learning Search Solve Create Share (SSCS) model. The research consist of two cycles, each cycle has four stages, which are planning, implementation, observation, and reflection. The subject is student of class XI IPS 1 SMAN 1 Bangkinang Kota in academic years 2018/2019, which total to 31 students. The instruments of data collection were observation sheets and students Mathematic tests. The observation sheets were analyzed in qualitatively, while the students Mathematic tests were analyzed in quantitatively. The qualitative descriptive showed an improvement of learning process after to the action on the first and second cycle. Most of students were very confidenced and active in learning process, they were finished mathemathic’s problems that given, presenting the result of problems and giving the conclusion of learning. Number of students that reach Minimum Mastery Criteria increase from basic score to first test I and II. The results of this research showed an increasing of students achievement where the basic score (25,81%) to the first test (48,39%) to the second test (74,19%). For the achievement of score the first test (41,93%) to the second test (87,09%). Results of this research indicates that application of the learning SSCS model can improve learning process and increase mathematics achievement of the students at class XI IPS 1 SMAN 1 Bangkinang Kota in academic years 2018/2019 for the subject matter linear programming and matrix.Key Words : Mathematics Achievement, Search Solve Create Share (SSCS)